Stylistic features of the translation of the poem by A. Chobat “Vaclav Ivanovsky” into Russian - Lamm Maria Andreevna (Studia Humanitatis)
The paper studies the features of the literary translation of the Belarusian poem and song “Vaclav Ivanovsky” into the Russian language. The translation considered the linguistic features of the poem translation between closely related languages and the genre originality of rock poetry. The translation was recorded as a song. A survey was conducted among the bearers of Russian culture in order to identify the features of the associative perception of the song text dedicated to a certain historical figure in a particular period.